Pemahaman Mengenai Penanganan Cedera Olahraga Melalui Sport Massage Dan Metode RICE Bagi Atlet Pencaksilat IPSI Kabupaten Pekalongan - putri, mega widya (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2022)
The purpose of this community service is to provide scientific knowledge in the field of handling sports injuries through sports massage and the rice method for pencak silat athletes in Pekalongan Regency theoretically and practically in increasing knowledge of handling sports injuries in the field. This community service is carried out in Pekalongan Regency. The material presented at this seminar is about handling sports injuries through sports massage and the rice method. The results of the implementation of this community service activity are expected to provide knowledge to athletes, especially pencak silat athletes in Pekalongan Regency and can produce quality masseurs for the recovery needs of athletes in Pekalongan Regency.